1956
DOI: 10.1507/endocrj1954.3.197
|View full text |Cite
|
Sign up to set email alerts
|

Investigation on Chick Assay Method for Avian Gonadotropins

Abstract: One of the major problems in studies on gonadotropin(GTH)is to use the appropriate assay method. While numerous methods of bio-assay for GTH were used by many workers, one of those was based on the weight-increases of gonad and accessory sexual organ of assay animals, and this might be classified into following three groups according to the species of assay animals;rat, mouse and chick method. Greep et al.(1936)and Cartland and Nelson(1938)concluded that gonads and accessory organs of immature rats suited to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1958
1958
1975
1975

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Nakajo & Imai (1956), comparing assays based on increases of ovarian and uterine weights in immature mouse or rat with the chick testis assay, reported that the latter was most sensitive for chicken gonadotrophin and adequate for use as quantitative assay when anterior pituitaries from cockerels or hens were used as the test substance. It is commonly accepted, however, that the increase in chick testis weight is not specific for either fsh or lh (Breneman, Zeller & Beekman, 1959).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nakajo & Imai (1956), comparing assays based on increases of ovarian and uterine weights in immature mouse or rat with the chick testis assay, reported that the latter was most sensitive for chicken gonadotrophin and adequate for use as quantitative assay when anterior pituitaries from cockerels or hens were used as the test substance. It is commonly accepted, however, that the increase in chick testis weight is not specific for either fsh or lh (Breneman, Zeller & Beekman, 1959).…”
Section: Discussionmentioning
confidence: 99%
“…1, total gonadotrophic activities of the anterior pituitary and the plasma extract were determined by the use of the chick testis assay described previously (Nakajo & Imai, 1956). In preliminary assays, the linearity of the dose-response line was held within the dose ranges of 1 to 8 mg acetone-dried pituitary powder and 8 to 32 mg plasma extract ofthe laying hen.…”
Section: Bioassaysmentioning
confidence: 99%
“…No difference was observed at 32 days of age. It has been reported that mammalian pituitary gonadotropins are not as effective for gonadal growth in birds as in mammals (Nakajo and Imai, 1956;Herrick et al, 1962). In previous experiments in this laboratory with coturnix kept in a photoresponsive state by being subjected to LD 8:16 from hatch to 2 weeks of age, the response to exogenous LH was greater than to FSH (Tanaka et al, 1966).…”
Section: Resultsmentioning
confidence: 89%
“…He found no close correlation between the number of these granules and the rate of lay, but he did not find these granules present in cocks and nonlayers. The significance of these granules is not known An assay method for avian gonadotrophins employing the chick has recently been described by Nakajo and Imai (1956). They compared the sensitivities of rats, mice, and chicks to anterior pituitary (cephalic lobe) from White Leghorn cocks, based upon changes in gonad size The chicks showed the highest sensitivity to the avian gonadotrophic hormones.…”
Section: Parathyroids and Estrogen In Regulation Of Blood And Shell Cmentioning
confidence: 99%